Nutrient uptake, Yield and Quality of Linseed (Linum usitatissimum L.) as affected by Fertility Levels and Seed Rates in Dryland Condition of Eastern Uttar Pradesh - Meena, Rang Lal; Singh, T. K.; Kumar, Rakesh; Kumar, Pramod (International Journal of Bio-resource and Stress Management, 2023)
A field trial was conducted during the rabi season of 2006 and 2007 at the Agronomic Research farm, Institute of Agricultural Sciences, Banaras Hindu University, Varanasi to assess the nutrient uptake, yield and quality of linseed as affected by fertility levels and seed rates in dryland condition of Eastern Uttar Pradesh in randomized block design with three replication. Results revealed that increase in fertility levels significantly increased N, P, K, S concentration in grain and straw, oil content, oil yield, protein content, protein yield. Increase in fertility levels resulted in significant increase in both seed and straw yield. However in case of seed rate, increase in seed rate significantly increase grain yield from 20kg to 30kg ha-1 but with further increase in seed rate, grain yield decreased while the straw yield was maximum with 40 kg seed rate. Increase in seed rate resulted significant decrease in oil content in grain. Total oil yield was increased with increase in seed rate upto 30 kg ha-1 after that it started to decrease. The NPKS content in seed and straw was significantly decreased with increased seed rate and found maximum with 20 kg seed rate.